How man-made interference might cause gas bubble emboli in deep diving whales - Fahlman, Andreas; Tyack, Peter L.; Miller, Patrick J.; Kvadsheim, Petter H. (Frontiers in Physiology, 2014)
Recent cetacean mass strandings in close temporal and spatial association with sonar activity has raised the concern that anthropogenic sound may harm breath-hold diving marine mammals. Necropsy results of the stranded whales have shown evidence of bubbles in the tissues, similar to those in human divers suffering from decompression sickness (DCS). It has been proposed that changes in behavior or physiological responses during diving could increase tissue and blood N2 levels, thereby increasing DCS risk. Dive data recorded from sperm, killer, long-finned pilot, Blainville’s beaked and Cuvier’s beaked whales before and during exposure to low- (1-2 kHz) and mid- (2-7 kHz) frequency active sonar were used to estimate the changes in blood and tissue N2 tension (PN2). Our objectives were to determine if differences in 1) dive behavior or 2) physiological responses to sonar are plausible risk factors for bubble formation. The theoretical estimates indicate that all species may experience high N2 levels. However, unexpectedly, deep diving generally result in higher end-dive PN2 as compared with shallow diving. In this focused review we focus on three possible explanations: 1) We revisit an old hypothesis that CO2, because of its much higher diffusivity, form bubble precursors that continue to grow in N2 supersaturated tissues. Such a mechanism would be less dependent on the alveolar collapse depth but affected by elevated levels of CO2 following a burst of activity during sonar exposure. 2) During deep dives, a greater duration of time might be spent at depths where gas exchange continues as compared with shallow dives. The resulting elevated levels of N2 in deep diving whales might also make them more susceptible to anthropogenic disturbances. 3) Extended duration of dives even at depths beyond where the alveoli collapse could result in slow continuous accumulation of N2 in the adipose tissues that eventually becomes a liability.